Empowering hearts and shaping destinies: unveiling the profound influence of education on women’s mate selection in Pakistan – a comprehensive mixed-methods study - Daraz, Umar; Khan, Younas; Alnajdawi, Ann Mousa; Alsawalqa, Rula Odeh (Frontiers in Sociology, 2023)
This study investigates the impact of education on women’s empowerment in the realm of mate selection within Malakand Division, Khyber Pakhtunkhwa, Pakistan. Employing a mixed-method research approach, the study conducted 30 semi-structured interviews with educated women and distributed a Likert Scale questionnaire to 500 women. The qualitative findings reveals that education significantly influences women’s perspectives, guiding their priorities, and instilling a desire for compatibility and shared values in their relationships. Educated women also display resilience, confidence, and a readiness to challenge prevailing societal norms and gender stereotypes when selecting a life partner. Quantitative analysis establishes a statistically significant positive correlation between education and women’s empowerment in mate selection. These findings underscore the pivotal role of education in enhancing women’s agency and autonomy in a critical aspect of their lives. The study’s implications extend to policy recommendations advocating for increased access to quality education and the implementation of gender-sensitive curricula in Malakand Division and analogous regions. Recognizing education’s potential to empower women in mate selection is vital for fostering a more equitable and inclusive society.